Occupational burdens in special educators working with intellectually disabled students - Piotr Plichta (Nofer Institute of Occupational Medicine, 2014)
Background: The article presents the results of psychosocial burdens in special educators (specialists in the field of oligophrenopedagogy) with intellectually disabled students. In theoretical part, specific context of occupational stress in special educators was introduced. Additionally, the need of broader research context regarding occupational stress and the risk of burnout in special educators working with intellectually disabled individuals were included. Material and Methods: The results were obtained using Plichta and Pyżalski's Questionnaire of Occupational Burdens in Teaching (QOBT). The presented results are based on a research sample (N = 100) of special educators (female) teaching intellectually disabled students attending special schools in the city of Łódź. The obtained results were compared with the results coming from a large random sample of public school teachers working with non-intellectually disabled children from the Łodź voivodeship (N = 429) and referred to the norms of QOBT. Results: The results show significant percentage of respondents obtaining high level of occupational burdens (conflict situations - 45%, organizational burdens - 31%, lack of work sense - 40%, global score - 40%). Seniority is not related to the level of burdens. Some significant differences concerning the level of occupational burdens between both groups of teachers were found. Conclusions: The study showed e.g. the strong need for supporting special educators in the workplace context and the need of implementing preventive and remedial measures at both individual and organizational levels (especially in terms of improving personal relationships in a workplace). Generally, the results show similarity of the stressors' ranking in special educators and school teachers working with non-intellectually disabled children. Med Pr 2014;65(2):239-250